Report of two siblings with spondylodysplastic Ehlers-Danlos syndrome and B4GALT7 deficiency - Delia Lorenz; Wolfram Kress; Ann-Kathrin Zaum; Christian P. Speer; Helge Hebestreit (BMC, 2021)
Abstract Background The spondylodysplastic Ehlers-Danlos subtype (OMIM #130070) is a rare connective tissue disorder characterized by a combination of connective tissue symptoms, skeletal features and short stature. It is caused by variants in genes encoding for enzymes involved in the proteoglycan biosynthesis or for a zinc transporter. Presentation of cases We report two brothers with a similar phenotype of short stature, joint hypermobility, distinct craniofacial features, developmental delay and severe hypermetropia indicative for a spondylodysplastic Ehlers-Danlos subtype. One also suffered from a recurrent pneumothorax. Gene panel analysis identified two compound heterozygous variants in the B4GALT7 gene: c.641G > A and c.723 + 4A > G. B4GALT7 encodes for galactosyltransferase I, which is required for the initiation of glycosaminoglycan side chain synthesis of proteoglycans. Conclusions This is a first full report on two cases with spondylodysplastic Ehlers-Danlos syndrome and the c.723 + 4A > G variant of B4GALT7. The recurrent pneumothoraces observed in one case expand the variable phenotype of the syndrome.